Are diffuse and limited juvenile systemic sclerosis different in clinical presentation? Clinical characteristics of a juvenile systemic sclerosis cohort. Issue 1 (February 2019) - Foeldvari, Ivan; Klotsche, Jens; Torok, Kathryn S; Kasapcopur, Ozgur; Adrovic, Amra; Stanevicha, Valda; Terreri, Maria Teresa; Alexeeva, Ekaterina; Katsicas, Maria; Cimaz, Rolando; Kostik, Mikhail; Lehman, Thomas; et al.
Introduction: Juvenile systemic sclerosis is an orphan disease. Currently, the majority of juvenile systemic sclerosis cohort studies are retrospective in design without standardized assessment. This study was conducted prospectively to investigate the difference in manifestations of limited cutaneous juvenile systemic sclerosis and diffuse cutaneous juvenile systemic sclerosis subtypes. An additional aim was to compare these data to other juvenile systemic sclerosis cohorts and a large adult systemic sclerosis cohort. Methods: Patients fulfilling the Paediatric Rheumatology European Society juvenile systemic sclerosis classification criteria were included. Clinical characteristics and patient-related outcomes were assessed. Results: In all, 88 patients with a mean disease duration of 3.5 years were enrolled, 72.5% with diffuse cutaneous juvenile systemic sclerosis with a mean modified Rodnan Skin score of 18 and 27.5% with limited cutaneous juvenile systemic sclerosis with mean modified Rodnan Skin score of 9. The mean age at the onset of Raynaud's and first non-Raynaud's symptoms was similar in both groups, approximately 9 and 10.5 years. Active digital tip ulcerations were present in 29% diffuse cutaneous juvenile systemic sclerosis and none in the limited cutaneous juvenile systemic sclerosis subjects (p = 0.005). Of those with cardiopulmonary testing, 3% of diffuse cutaneous juvenile systemic sclerosis and 23% of limited cutaneous juvenile systemic sclerosis group had cardiac involvement (p = 0.015), and 41% diffuse cutaneous juvenile systemic sclerosis and 22% of the limited cutaneous juvenile systemic sclerosis group had pulmonary involvement (p = 0.009). Physician global disease damage assessment was higher in the diffuse cutaneous juvenile systemic sclerosis group compared to the limited cutaneous juvenile systemic sclerosis group: 35 and 15 (p = 0.021). Discussion: The majority of this international juvenile systemic sclerosis cohort had diffuse cutaneous juvenile systemic sclerosis (72.5%) with more frequent vascular and pulmonary involvement compared to the limited cutaneous group, who had increased cardiac involvement. Our cohort reflects prior findings of published juvenile systemic sclerosis cohorts and emphasizes a difference in the presentation compared to adult-onset systemic sclerosis.